1996
DOI: 10.1007/bf00208304
|View full text |Cite
|
Sign up to set email alerts
|

Feed-back regulation of gibberellin biosynthesis and gene expression in Pisum sativum L.

Abstract: Treatment of tall and dwarf (3 beta-hydroxylase impaired) genotypes of pea (Pisum sativum L.) with the synthetic, highly active gibberellin (GA), 2,2-dimethyl GA4, reduced the shoot contents of C19-GAs, including GA1, and increased the concentration of the C20-GA, GA19. In shoots of the slender (la crys) mutant, the content of C19-GAs was lower and GA19 content was higher than in those of the tall line. Metabolism of GA19 and GA20 in leaves of a severe (na) GA-deficient dwarf mutant was reduced by GA treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
90
2
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(100 citation statements)
references
References 23 publications
7
90
2
1
Order By: Relevance
“…In the DELLA slender mutants sln in barley , slr1 in rice (Itoh et al, 2002), and la cry-s in pea (Potts et al, 1985;Martin et al, 1996), the synthesis of bioactive GAs is reduced, but this has only been shown for shoots. We therefore monitored the expression of GA biosynthesis and deactivation genes in the roots of wild-type and slender pea plants.…”
Section: Discussionmentioning
confidence: 99%
“…In the DELLA slender mutants sln in barley , slr1 in rice (Itoh et al, 2002), and la cry-s in pea (Potts et al, 1985;Martin et al, 1996), the synthesis of bioactive GAs is reduced, but this has only been shown for shoots. We therefore monitored the expression of GA biosynthesis and deactivation genes in the roots of wild-type and slender pea plants.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the regulation of elongation growth (described above), it has been suggested that Pfr might suppress GA biosynthesis. GA 20-oxidase transcript levels are subject to feedback regulation (Phillips et al, 1995;Martin et al, 1996;Toyomasu et al, 1997); GAdeficient mutants accumulate a high level of 20-oxidase mRNA, which is markedly reduced by application of bioactive GA. Our preliminary experiments showed that, similar to Ls20ox2, the expression of the Ls20ox1 and Ls3h1 genes, which were not negatively regulated by far-red-/ red-light treatment, was markedly decreased by treatment with GA 1 (data not shown). Furthermore, we cannot yet say whether the endogenous GA 1 generated within 3 h of incubation after a far-red-/red-light treatment is sufficient for negative feedback regulation to achieve the observed decrease in the Ls20ox2 transcript levels.…”
Section: Discussionmentioning
confidence: 99%
“…Ps074 (no. X91658) (Martin et al, 1996), At2301 (no. X83379) (Phillips et al, 1995), and Cm20ox (no.…”
Section: Northern-blot Analysismentioning
confidence: 99%
“…Recent experiments have shown that in normal plants endogenous GA levels are homeostatically controlled via GA-mediated negative feedback regulation (Hedden and Croker, 1992). As a part of this process, the expression of a number of the genes encoding enzymes involved in GA biosynthesis is downregulated by GA (Chiang et al, 1995;Phillips et al, 1995;Xu et al, 1995;Martin et al, 1996;Hedden and Kamiya, 1997;Cowling et al, 1998). This down-regulation is perturbed in gai (Talon et al, 1990a;Xu et al, 1995;Peng et al, 1997), thus explaining the increased endogenous GA levels in gai and indicating the involvement of GAI (the GAI gene product) in the homeostatic regulation of GA levels.…”
mentioning
confidence: 99%